Behavioral and Molecular Effects Induced by Cannabidiol and Valproate Administration in the GASH/Sal Model of Acute Audiogenic Seizures - Cabral-Pereira, Giselda; Sánchez-Benito, David; Díaz-Rodríguez, Sandra M.; Gonçalves, Jaime; Sancho, Consuelo; Castellano, Orlando; Muñoz, Luis J.; López, Dolores E.; Gómez-Nieto, Ricardo (Frontiers in Behavioral Neuroscience, 2021)
Despite evidence that supports cannabidiol (CBD) as an anticonvulsant agent, there remains controversy over the anti-seizure efficacy, possible adverse effects, and synergistic interactions with classic antiepileptics such as valproate (VPA). The genetic audiogenic seizure hamster from the University of Salamanca (GASH/Sal) is a reliable experimental model of generalized tonic-clonic seizures in response to intense sound stimulation. The present study examines the behavioral and molecular effects of acute and chronic intraperitoneal administrations of VPA (300 mg/Kg) and CBD (100 mg/kg) on the GASH/Sal audiogenic seizures as well as the co-administration of both drugs. The GASH/Sal animals were examined prior to and after the corresponding treatment at 45-min, 7-days and 14-days for seizure severity and neuroethology, open field behaviors, body weight variations as well as various hematological and biochemical parameters. Furthermore, the brain tissue containing the inferior colliculus (so-called epileptogenic nucleus) was processed for RT-qPCR analysis to determine the treatment effects on the gene expression of neuronal receptors associated with drug actions and ictogenesis. Our results indicated that single-dose of VPA helps prevent the animals from getting convulsions, showing complete elimination of seizures, whereas 7-days of chronic VPA treatment had few effects in seizure behaviors. Acute CBD administration showed subtle attenuation of seizure behaviors, increasing seizure latency and decreasing the duration of the convulsion phase, but without entirely seizure abolition. Chronic CBD treatments had no significant effects on sound-induced seizures, although some animals slightly improved seizure severity. Acute and chronic CBD treatments have no significant adverse effects on body weight, hematological parameters and liver function, although locomotor activity was reduced. The combination of VPA and CBD did not alter the therapeutic outcome of the VPA monotherapy, showing no apparent synergistic effects. As compared to sham animals, chronic treatments with CBD caused abnormal mRNA expression levels for Trpv1, Adora1, Slc29a1 and Cnr1 genes, whereas no differences in gene expression was found for Htr1a and Sigmar1. Our study shed light on the behavioral and molecular effects of CBD and VPA on the GASH/Sal model, and constituted the basis to develop further studies on the pharmacological effects of CBD and its interactions with other anticonvulsants.